2015
DOI: 10.3846/13926292.2015.1064486
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of Biological Tissues During Cryosurgery Using Hyperbolic Heat Conduction Model

Abstract: Abstract. This paper considers hyperbolic heat conduction model for biological tissue freezing during cryosurgery with non ideal property of tissue, metabolism and blood perfusion. Mathematical model is solved numerically using finite difference method to obtain temperature distribution and phase change interfaces in tissue during freezing. The effects of phase lag of heat flux in hyperbolic bio-heat model on freezing process are studied. Comparative study of parabolic and hyperbolic bio-heat models is also ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The value of the thermal relaxation time in biological bodies has been predicted to be within 20-30 s [33]. It was found that the non-Fourier model provides a more adequate description of unsteady heat transfer processes occurring in the nonhomogeneous materials such as biological tissue [21,[34][35][36][37][38][39][40][41][42][43].…”
Section: Direct Problemmentioning
confidence: 99%
“…The value of the thermal relaxation time in biological bodies has been predicted to be within 20-30 s [33]. It was found that the non-Fourier model provides a more adequate description of unsteady heat transfer processes occurring in the nonhomogeneous materials such as biological tissue [21,[34][35][36][37][38][39][40][41][42][43].…”
Section: Direct Problemmentioning
confidence: 99%
“…Other formulas applied to the bioheat transfer issue are the Pennes equation [ 21 ], the Cattaneo–Vernotte equation [ 22 , 23 , 24 ], and the dual phase lag (DPL) model. Bioheat transfer modelling describes phenomena that occur not only during cryopreservation by slow freezing [ 17 ] and vitrification [ 12 , 15 , 25 ], but also other examples of thermal process modelling applications, such as the characterisation of cryosurgery [ 26 , 27 , 28 , 29 , 30 ] or the destruction of biological tissue under the influence of a magnetic field [ 11 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the modelling of phase transitions can be found in the literature [5,[9][10][11][12][13][14]. As can be seen, most of them present models related to cryosurgery.…”
Section: Introductionmentioning
confidence: 99%